Long-Term Outcomes of Cervical Laminoplasty in the Elderly. (25th October 2015) - Oshima, Yasushi; Miyoshi, Kota; Mikami, Yoji; Nakamoto, Hideki; Tanaka, Sakae
Abstract : Incidences of cervical laminoplasty in the elderly are increasing; the influence of other age-related complications and neurological status must be considered for justifying surgery. This study identified the aforementioned influence on long-term outcomes of cervical laminoplasty in patients aged ≥75 years. Thirty-seven of 38 consecutive patients aged ≥75 years who underwent cervical laminoplasty were retrospectively evaluated. Minimum 5-year follow-up was acceptable if patients were complication-free. Follow-up was terminated when neurological evaluation was not possible, owing to death or other serious complications affecting activities of daily living (ADL). Postoperative neurological changes and newly developed severe complications were investigated. Postoperatively, one patient died of acute pneumonia, one remained nonambulatory owing to cerebral infarction, and 35 were ambulatory and were discharged. At a mean follow-up of 78 months, three patients died and nine developed serious complications severely affecting ADL. Of the 25 remaining patients, 23 remained ambulatory at mean follow-up of 105 months. Cox proportional hazard analysis revealed that postoperative motor upper and lower extremities JOA scores of ≤2 and ≤1, respectively, were risk factors for mortality or other severe complications. Postoperative neurological status can be maintained in the elderly if they remain complication-free. Poorer neurological status significantly affected their ADL and mortality.